Constitutional Enforcement and Justice in the Determination of Political Parties (Parpol) as Participants in the 2024 Indonesian Elections - Didik Suhariyanto (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
This research discusses the enforcement of the constitution and justice in the determination of political parties as participants in the general elections in Indonesia in 2024. Given the critical role of political parties in democratic processes, understanding the challenges in their registration is essential for enhancing electoral integrity. The method used in this research is qualitative research. Specifically, the data and information related to this research were collected through a comprehensive literature study. Through an in-depth analysis of the political party registration process, this research identifies a number of challenges and obstacles faced, including technical problems in the application of information technology, a lack of administrative understanding by political parties, and a mismatch in treatment between parliamentary and non-parliamentary parties. In addition, the research also highlights the government's role in overseeing and facilitating the institution of political parties in line with the principles of financial accountability and transparency. The findings suggest that technical issues and administrative disparities must be addressed to ensure fair competition among parties. As such, this research makes an important contribution to efforts to improve the integrity and credibility of Indonesia's political system, moving towards more inclusive, transparent, and fair elections. The implications of these findings are significant for policymakers and electoral bodies aiming to strengthen democratic processes in Indonesia.